2019
DOI: 10.1039/c9cp02113b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the F(2P) + NH3→ HF + NH2reaction on an accurate potential energy surface: dynamics and kinetics

Abstract: Competition of the direct and indirect mechanisms in the hydrogen abstraction reaction between F and NH3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 42 publications
3
51
0
Order By: Relevance
“…As discussed in a previous publication, 25 the neutral PES is constructed by fitting ~41000 ab initio energy points calculated at the unrestricted coupled cluster level with singles, doubles, and perturbative triples 52 with Dunning's augmented correlation-consistent polarized valence triple zeta basis set 53 and core electrons frozen (FC-UCCSD(T)-F12a/aug-cc-pVTZ) using the fundamental-invariant neural network (FI-NN) method. 54 An anion PES is newly constructed for this work by fitting a total of ~11000 energy points at the same level of theory used to construct the neutral PES.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in a previous publication, 25 the neutral PES is constructed by fitting ~41000 ab initio energy points calculated at the unrestricted coupled cluster level with singles, doubles, and perturbative triples 52 with Dunning's augmented correlation-consistent polarized valence triple zeta basis set 53 and core electrons frozen (FC-UCCSD(T)-F12a/aug-cc-pVTZ) using the fundamental-invariant neural network (FI-NN) method. 54 An anion PES is newly constructed for this work by fitting a total of ~11000 energy points at the same level of theory used to construct the neutral PES.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…1) has recently been determined by fitting a large number of high-level ab initio points in full dimensionality. 25 Previous experimental work on the title reaction has studied the vibrational distribution of the HF product via infrared chemiluminescence [26][27][28] More recent crossed beam experiments by Yang and co-workers 29 have shown that the HF products (or DF in the F + ND3 reaction) are largely forward scattered with respect to the incoming F atom. Quasi-classical trajectory studies on the dynamics and kinetics of this reaction have been reported on an analytical PES, [30][31] and the calculated differential cross sections agreed reasonably well with the values determined by Yang.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, while Walther and Wigner in 1983 [38] reported that the rate constants were practically independent of temperature in the range 250-369 K (where large uncertainties are present), Persky [39] reported inverse temperature dependence in the range 276-327 K in 2007. Theoretically, this reaction has also been studied [40][41][42][43][44][45][46][47]. In 1997, our lab developed the first analytical potential energy surface for this reactive system, PES-1997, which was semiempirical, i.e., it was fitted to theoretical and experimental information [42].…”
Section: The F( 2 P) + Nh3 Reaction: Does a Huge Number Of Points Gua...mentioning
confidence: 99%
“…This assumption remains speculative even if the work from Ogawa [15] indirectly suggests that NH4F could be produced from the reaction of NH3 gas with some fragment of NF3 (formed by heating NF3). As a matter of fact, the formation of HF in the plasma can be expected to play a significant role in the overall chemistry and we can expect HF to be formed by the chain reactions (2-4) (well known in HF laser physics) [25,26,27,28,29,30]:…”
Section: Several Innovative Etching Processes Have Been Developed Recmentioning
confidence: 99%